La Norma Internacional de Información Financiera N° 15 y su incidencia en los estados financieros en la empresa ECCONSA período 2019-2020 - Rodríguez Ruíz, Dennys Paúl (2025)
The International Financial Reporting Standard No. 15 (IFRS 15), titled Revenue from Contracts with Customers, establishes a standard model for revenue recognition, providing greater transparency and comparability in financial statements. Its application at ECCONSA during the 2019–2020 period had a significant impact on the presentation and analysis of its financial statements, requiring a detailed approach to identifying and measuring revenue related to its contracts. IFRS 15 is based on five essential steps: identifying the contract with the customer, determining the performance obligations, establishing the transaction price, allocating the price to each obligation, and recognizing revenue when those obligations are fulfilled. This methodology promotes revenue recognition based on the company’s actual performance, instead of relying on traditional accounting practices that could create discrepancies. At ECCONSA, the implementation of IFRS 15 required adjustments in how revenue from long-term contracts and contracts with variable payments was accounted for. This primarily affected revenue classification, price estimates, and the evaluation of obligation fulfillment. As a result, changes were evident in operating margins and in the presentation of income statements, reflecting the company’s financial performance more accurately. Additionally, IFRS 15 required a review of internal control systems. The impact of this standard not only improved the quality of the financial information presented but also increased investor and stakeholder confidence by providing reports more aligned with international accounting principles. In conclusion, IFRS 15 marked a significant change in ECCONSA's financial processes, contributing to greater transparency and uniformity in financial reporting.